2023
DOI: 10.1021/acs.jpcc.2c07737
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Structure–Function Relationship in Fluorine-Functionalized MOFs for PFOA Capture from Water

Abstract: A strategy that can be used to develop metal− organic frameworks (MOFs) to capture per-and poly-fluoroalkyl substances (PFAS) from water is functionalizing them with fluorine moieties. We investigated different fluorine-functionalization strategies and their performance in removing PFAS from water using molecular simulations. Perfluorooctanoic acid (PFOA), one of the most widely encountered PFAS in water sources, was used as the probe molecule. Our simulations show that fluorine functionalization by incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…With the strong affinity of fluorine taken into account, the structure of MOFs was modified through fluorine functionalization. 85 Kong et al 86 synthesized fluorine-functionalized MOFs for the purpose of removing of PFOA from water. Fluorine groups offer high selectivity in terms of adsorption sites for PFOA, resulting in an adsorption capacity of 185.151 μmol/g.…”
Section: Performance Of Mofs For Pfassmentioning
confidence: 99%
See 1 more Smart Citation
“…With the strong affinity of fluorine taken into account, the structure of MOFs was modified through fluorine functionalization. 85 Kong et al 86 synthesized fluorine-functionalized MOFs for the purpose of removing of PFOA from water. Fluorine groups offer high selectivity in terms of adsorption sites for PFOA, resulting in an adsorption capacity of 185.151 μmol/g.…”
Section: Performance Of Mofs For Pfassmentioning
confidence: 99%
“…With the strong affinity of fluorine taken into account, the structure of MOFs was modified through fluorine functionalization . Kong et al synthesized fluorine-functionalized MOFs for the purpose of removing of PFOA from water.…”
Section: Strategies To Improve the Removal Performance Of Mofs For Pfassmentioning
confidence: 99%
“…Erkal et al [ 71 ] reported on MOFs functionalized with fluorine atoms to capture PFASs. In this study, the authors used DFT to complete geometry optimizations of the structures.…”
Section: Adsorbents and Morphologymentioning
confidence: 99%
“…The introduction of fluorine atoms into organic molecules (usually replacing hydrogen) imparts a unique set of physicochemical properties that often enhance pharmacokinetic profiles, metabolic stability, and receptor interactions but keep many of the good properties of the parent compounds. On the other hand, per- and polyfluoroalkyl substances (PFAS) have garnered unprecedented attention in recent years, becoming a focal point of scientific inquiry, regulatory concern, and public discourse. These synthetic compounds, characterized by their remarkable stability and hydrophobic nature, open new perspectives in industrial and commercial applications. , However, their persistent presence in the environment, coupled with potential adverse health effects, has propelled PFAS to the forefront of global environmental and health agendas. Thus, it seems clear that a detailed theoretical understanding of fluorinated organic drugs and PFAS, in particular their thermodynamic properties and kinetic stability, is of high general interest. …”
Section: Introductionmentioning
confidence: 99%
“…10−12 These synthetic compounds, characterized by their remarkable stability and hydrophobic nature, open new perspectives in industrial and commercial applications. 13,14 However, their persistent presence in the environment, coupled with potential adverse health effects, has propelled PFAS to the forefront of global environmental and health agendas. Thus, it seems clear that a detailed theoretical understanding of fluorinated organic drugs and PFAS, in particular their thermodynamic properties and kinetic stability, is of high general interest.…”
Section: Introductionmentioning
confidence: 99%